KONVERSI SAMPAH ORGANIK DAPUR MENJADI CAIRAN MULTIGUNA GARBAGE ENZYMES DI WILAYAH SIRING AGUNG KOTA PALEMBANG - Dian Kharismadewi; Innike Abdillah Fahmi; Sri Martini; Muhammad Andika Mandala Putra (LP2M Universitas Hasanuddin, 2022)
Environmentalism efforts by performing the household waste management that carried out the 4R (reduce, reuse, recycle, and replace), go green, back to nature. Zero waste concepts must continue to be encouraged and disseminated to the broader community. One of those possible efforts is to convert the organic wastes from the household kitchen into multipurpose liquid garbage enzymes. Garbage enzyme is a liquid containing extract from the fermentation process of the vegetable’s dregs and fruit’s peels, with brown sugar/molasses as a substrate and water as a ripening medium. Fermentation processes proceed for three months and are stored in an airtight container. Garbage enzyme is then used as a liquid cleaner and fertilizer for plants. Siring Agung sub-urban district in Kota Palembang is a densely populated area that has faced a problem of many organic wastes that burden the environment as a result of the overloaded work of garbage dumpsites. Through socialization in the form of a presentation and demonstration of making a multipurpose liquid garbage enzyme, the community in Siring Agung of Palembang city could implement the environmentally-friendly organic waste processing concepts and provide solutions to waste problems in this area. The specific purpose of this community service is to determine the level of public understanding regarding the conversion and utilization of household organic waste and assess the program's benefits in solving problems in this target area. Besides, to reduce the burden of landfills in Palembang city, maintain environmental sustainability, and spread the benefits of garbage enzymes. The analysis results of the public understanding of waste management are 76% understanding after the socialization. This activity has offered an advantage to the community as new applicable knowledge. This activity has provided benefits to the community in the form of new knowledge that can be applied and the reduction of household organic waste, which is a problem in this area. — Upaya pelestarian lingkungan melalui pengelolaan sampah rumah tangga yang mengusung konsep 4R (reduce, reuse, recycle, dan replace), go green, back to nature, dan zero waste harus terus digalakkan dan disosialiasikan ke masyarakat luas. Salah satu upaya yang mungkin dilakukan adalah dengan mengubah sampah organik dari dapur rumah tangga menjadi cairan multiguna Garbage Enzyme. Garbage enzyme adalah cairan yang berisi ekstrak dari proses fermentasi potongan sayuran sisa dan kulit buahan, yang telah ditambahkan dengan substrat gula merah dan air sebagai media pematangannya. Proses fermentasi dilakukan selama 3 bulan dan disimpan didalam wadah kedap udara. Garbage enzyme yang dihasilkan dimanfaatkan menjadi cairan pembersih dan pupuk cair tanaman. Kelurahan Siring Agung Kota Palembang merupakan wilayah yang padat penduduk yang memiliki permasalahan sampah organik yang mengganggu lingkungan dari beban penampungan sampah yang berlebihan. Melalui sosialisasi dalam bentuk pemaparan dan demo pembuatan cairan multiguna garbage enzyme, masyarakat wilayah Siring Agung Kota Palembang dapat menerapkan konsep pengolahan sampah organik yang ramah lingkungan dan mengatasi permsalahan sampah di wilayahnya. Tujuan khusus dari kegiatan PkM ini adalah untuk mengetahui tingkat pemahaman masyarakat mengenai pengkonversian dan pemanfaatan sampah organik rumah tangga serta menilai kebermanfaatan program yang dilaksanakan terhadap penyelesaian masalah yang ada diwilayah sasaran. Selain untuk mengurangi beban tempat pembuangan akhir sampah di Kota Palembang, menjaga kelestarian lingkungan, dan menebarkan manfaat garbage enzyme. Dari hasil analisa tingkat pemahaman masyarakat dalam pengelolaan sampah didapatkan 76% paham setelah dilakukan sosialisasi. Kegiatan ini telah memberikan manfaat kepada masyarakat berupa pengetahuan baru yang dapat diterapkan dan pengurangan sampah organik rumah tangga yang menjadi permasalahan di wilayah ini.